Wind energy modeling and simulation. Volume 1, - Veers, Paul S. (IET energy engineering series ;, 2019)
The book consists of 9 chapters and covers the following topics: exascale computing; blade-resolved modeling; mesoscale atmosphere modeling; wind plant simulation; atmospheric turbulence modelling; wind-farm flows; wind-plant-controller design; wind power forecasting and wind energy modeling.